Luppar: An Information Retrieval System for Closed Document Collections - da Silva, Fabiano Tavares; Maia, José Everardo Bessa (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e Computacional, 2018)
This article presents Luppar, an Information Retrieval tool for closed collections of documents which uses a local distributional semantic model associated to each corpus. The system performs automatic query expansion using a combination of distributional semantic model and local context analysis and supports relevancy feedback. The performance of the system was evaluated in databases of different domains and presented results equal to or higher than those published in the literature.